Studi Analisis Beban Kantilever Pada Baja Ringan - Wicaksono, Heru; Sartika, Dewi; Rubiono, Gatut (Prodi Teknik Mesin Universitas PGRI Banyuwangi, 2019)
Mild steel is one type of conventional roof frame replacement that is usually made of wood. The roof frame is increasingly used and more also in the market with various qualities and prices offered. The lightweight steel frame started replacing the wood that was from before until now already used for a skeleton on the roof building house, researchers aim to get a strong test result of weight lifting against mild steel. The cantilever test I used is a one-sided cantilever test. Where the test uses a one-sided clamp focus aimed at the steel to be tested can be hung. The results showed that the average on Lendutan resulting from the three variables in the cantilever had varying levels of cutaneous. The first variable with an average of 1.45 mm Lendutan, the second variable with an average 2.07 mm leading, the third variable with an average 2.52 mm leading. From the results of a three-variable comparison, that the lowest degree of solidity is found in the wedge material with the form of lath X with a yield of 1.45 mm of sloth.